Analisis Laporan Realisasi Anggaran Untuk Menilai Kinerja Keuangan Pemerintah Daerah Kabupaten Magelang Tahun 2019-2021 - Ruqidul Hajah Alhabsi; Nuwun Priyono; Risma Wira Bharata (Jurnal Riset Akuntansi, 2023)
This research was conducted to analyze the financial performance of the Magelang Regency Government in 2019-2021. This study uses financial ratio analysis, namely the effectiveness ratio and efficiency ratio. The research method used is descriptive qualitative using Magelang Regency Budget Realization Report (LRA) data for 2019-2021. From this research, it was faound that in 2019 the effectiveness rate was 94.52%, the efficiency rate was 89.98%, then in 2020 it had an effectiveness ratio of 124.21% and an efficiency ratio of 89.61% and in 2021 it had an effectiveness ratio of 103.71% and an efficiency ratio of 87.89%. Based on the results of the research that has been done, the Regional Government of Magelang Regency is expected to be able to carry out an evaluation by looking at the ratio of effectiveness and efficiency for the coming year.